Stone Trees Transplanted? Central Mexican Stelae of the Epiclassic and Early Postclassic and the Question of Maya 'Influence' - Jordan, Keith (Archaeopress Pre-Columbian Archaeology Ser., 2014)
Stelae dating to the Epiclassic (650-900 CE) and Early Postclassic (950-1150 CE) from Tula, Xochicalco, and other sites in Central Mexico have been presented in the archaeological and art historical literature of the last four decades, when they have been addressed at all, as evidence of classic Maya 'influence' on Central Mexican art during these periods. This book re-evaluates these claims via detailed comparative analysis of the Central Mexican stelae and their claimed Maya counterparts.